Pembinaan Guru-Guru di Pulau Tidung Melalui Seminar Deep Learning pada Pembelajaran Abad 21: Teacher Training on Tidung Island Through a Seminar on Deep Learning in 21st Century Education - Aeni, Ani Nur; Hanifah, Nurdinah; Rukmana, Kusman; Sujana, Atep (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Deep learning in a pedagogical context is an in-depth learning approach that involves essential understanding, emotional engagement, and the reinforcement of values and character. In practice, not all teachers have a sufficient understanding of this deep learning approach. This service project aims to improve teachers' understanding of Deep Learning in 21st-century learning on Tidung Island. The activity was conducted as a 32-hour seminar held over three days, from June 10 to 12, 2025, in a hybrid format combining in-person and online sessions. A total of 48 teachers from public elementary schools and kindergartens on Tidung Island participated in the seminar. The event was held at SD Negeri Pulau Tidung 01 Pagi, located in the Thousand Islands archipelago. The seminar materials included: 1) What is Deep Learning?, 2) Deep Learning in 21st-Century Education, 3) The Application of AI in Education: Strategies and Practices of Deep Learning in the Curriculum, and 4) Enhancing Literacy Through Deep Learning, presented by four speakers. The seminar results indicated that teacher training was conducted on Tidung Island through a seminar, and that the seminar increased teachers' understanding of deep learning in 21st-century learning.